Keterlibatan Badan Usaha Dalam Upaya Pencegahan Korupsi Korporasi Bagi Pelaku Bisnis Di Indonesia - Teti Mubarokah; Asrizal Asrizal (Lembaga Pengembangan Kinerja Dosen, 2024)
It cannot be denied that corruption is a special crime that threatens the survival of the state and nation, hinders development, and causes high economic costs and other negative impacts. This article's research method uses a qualitative analysis method, descriptive analysis combined with library research methods, to analyze laws and regulations related to the main problem. The discussion focuses on the scope of policies and regulations relevant to the business world and best practices for prevention efforts that can be carried out by the business world. Regulations prohibiting corporate criminal acts are clearly regulated, and business entities that commit corporate criminal acts can be held criminally responsible. Companies can implement anti-corruption programs in various ways. To increase the effectiveness of efforts to prevent corporate corruption, corporate anti-corruption programs need to be risk-based, communicative, dynamic, and continuously evaluated through measuring the success of appropriate internal steps and collaborative activities.